2020
DOI: 10.1108/tqm-10-2019-0241
|View full text |Cite
|
Sign up to set email alerts
|

Mobile chat servitization in the customer journey: from social capability to social suitability

Abstract: PurposeMobile instant messaging (MIM) is changing how we communicate with customers transforming what we used to buy as products into services. Servitization is the strategy by which the services offered in combination with a product become a central part of the offer and the value. This paper aims to focus on a new way to do business by means of mobile conversational commerce identified as a unique touchpoint for customers who wish to experience the product/service.Design/methodology/approachThis research use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 58 publications
2
23
0
1
Order By: Relevance
“…Customer engagement is beneficial for a tourism business as it leads to positive outcomes such as self‐brand connection and brand usage intention (Harrigan et al, 2018;, attachment (Li et al, 2020), corporate reputation (Dijkmans et al, 2015), customer trust, loyalty, and evaluations of tourism brands (So et al, 2016, 2020). Customer engagement is generally considered a fundamental metric of digital customer relationship management and a source of competitive advantage (Hao, 2020; Lo Presti et al, 2020). Marketing research has shown it affects consumers' electronic word of mouth (eWOM), attitude, intentions, and behaviors (Brodie et al, 2011; Chu et al, 2019; Giakoumaki & Krepapa, 2020; Hepola et al, 2020; Hollebeek et al, 2014; Levy & Gvili, 2020; Marino & Lo Presti, 2018; 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Customer engagement is beneficial for a tourism business as it leads to positive outcomes such as self‐brand connection and brand usage intention (Harrigan et al, 2018;, attachment (Li et al, 2020), corporate reputation (Dijkmans et al, 2015), customer trust, loyalty, and evaluations of tourism brands (So et al, 2016, 2020). Customer engagement is generally considered a fundamental metric of digital customer relationship management and a source of competitive advantage (Hao, 2020; Lo Presti et al, 2020). Marketing research has shown it affects consumers' electronic word of mouth (eWOM), attitude, intentions, and behaviors (Brodie et al, 2011; Chu et al, 2019; Giakoumaki & Krepapa, 2020; Hepola et al, 2020; Hollebeek et al, 2014; Levy & Gvili, 2020; Marino & Lo Presti, 2018; 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Customer engagement is beneficial for a tourism business as it leads to positive outcomes such as self-brand connection and brand usage intention (Harrigan et al, 2018;, attachment (Li et al, 2020), corporate reputation (Dijkmans et al, 2015), customer trust, loyalty, and evaluations of tourism brands (So et al, 2016(So et al, , 2020. Customer engagement is generally considered a fundamental metric of digital customer relationship management and a source of competitive advantage (Hao, 2020;Lo Presti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the interaction and customization of the message, the firm is, therefore, able to manage a business relationship before, during and after the purchase (Sotolongo and Copulsky, 2018). Lo Presti et al (2020) shows that through the use of IM in the business it is possible to follow the entire customer journey and trigger the customer engagement cycle, to promote satisfaction and loyalty to the channel.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, businesses can use IM and exploit the interaction to encourage the engagement and participation of the customer. Although IM platforms and social media networks, in general, are the venues for dialogue and the latter, in turn, is a strategic part of engagement (Taylor and Kent, 2014) and although studies acknowledge IM in business as a useful touch-point in activating customer engagement (Lo Presti et al , 2020), empirical studies that show the firm’s attitudes towards IM for marketing practices remain rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation